As novas faces do sindicalismo rural Brasileiro: a Reforma Agrária e as tradições sindicais na zona da Mata de Pernambuco - Marcelo Rosa (Universidade do Estado do Rio de Janeiro, 2004)
This article seeks to understand the fact that Pernambucan unionists have joined occupations of land, as well as the consequences of this new practice for the labour movement in other states where the Landless Workers' Movement (MST) is a monopoly force. Based on a systematic study of events organized by FETAPE (the rural labour federation of Pernambuco), it emerges that this traditional labour organization started to follow the model forged by the MST guided in large part by its internal union education structures, historic conditions of reproduction and especially by generational conflict between its members.